Exchange Rate, GDP and Inflation: Their Impact on Extreme Poverty in Indonesia - Puspitasari, Sindi Dewi; Adianata, Happy; Azhari, Azhari; Ahmed, Ishfaq (Economics Department, Faculty of Economic and Islamic Business, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
This study simultaneously analyzes how the rupiah exchange rate, gross domestic product and inflation affect extreme poverty in Indonesia over the period 2003-2023. The novelty of this study lies in the long-term approach that examines the dynamic interaction of the three variables together, which has not been widely studied in the context of extreme poverty in Indonesia. The impact of this research in the future is expected to be the basis for a more comprehensive economic policy that focuses on exchange rate stability, overall economic growth, and inflation control to reduce extreme poverty sustainably. Using a quantitative approach and multiple linear regression analysis, it was found that exchange rate stability and GDP growth support poverty reduction, while inflation worsens the condition of vulnerable groups. This study found that exchange rate strengthening and GDP growth have a significant effect in reducing extreme poverty by increasing people's purchasing power and income. In contrast, inflation exacerbates extreme poverty by depressing the purchasing power of vulnerable groups. This emphasizes the importance of exchange rate stability, inclusive economic growth, and inflation control. The findings highlight the need for policies that maintain exchange rate stability, promote inclusive economic growth, and control inflation to effectively reduce extreme poverty in Indonesia. The implications of this study suggest that the government needs to integrate economic strategies that focus on stability and inflation control in poverty alleviation policies, especially to improve the welfare of low-income groups.